Classifying Intersex in DSM-5: Critical Reflections on Gender Dysphoria - Kraus, Cynthia (Archives of sexual behavior, 2015)
The new diagnosis of Gender Dysphoria (GD) in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2013 ) defines intersex, renamed “Disorders of Sex Development” (DSD), as a specifier of GD. With this formulation, the status of intersex departs from prior editions, especially from the DSM-IV texts that defined intersex as an exclusion criterion for Gender Identity Disorder. Conversely, GD—with or without a DSD—can apply in the same manner to DSD and non-DSD individuals; it subsumes the physical condition under the mental “disorder.” This conceptualization, I suggest, is unprecedented in the history of the DSM. In my view, it is the most significant change in the revised diagnosis, and it raises the question of the suitability of psychiatric diagnosis for individuals with intersex/DSD. Unfortunately, this fundamental question was not raised during the revision process. This article examines, historically and conceptually, the different terms provided for intersex/DSD in the DSM in order to capture the significance of the DSD specifier, and the reasons why the risk of stigma and misdiagnosis, I argue, is increased in DSM-5 compared to DSM-IV. The DSM-5 formulation is paradoxically at variance with the clinical literature, with intersex/DSD and transgender being conceived as incommensurable terms in their diagnostic and treatment aspects. In this light, the removal of intersex/DSD from the DSM would seem a better way to achieve the purpose behind the revised diagnosis, which was to reduce stigma and the risk of misdiagnosis, and to provide the persons concerned with healthcare that caters to their specific needs.